What motivates South African parents (non-native English speakers) to teach their children English instead of their mother tongue - Makwakwa, Mona (My University, 2019)
This study is set within the field of sociolinguistics and aims to bring awareness to how language shift, language maintenance, language ideologies, and language attitudes are a significant factor when it comes to the perseveration of languages. The study aimed to answer the following questions: what motivates South African parents (non-native English speakers) to teach their children English instead of their mother tongue? If there was a significant relationship between people’s identity and their linguistic choices and what value parents attach to English vs. indigenous languages? There is a thin body of literature on language shift, language death, and how language choice affects parents choices when it pertains to the languages they use to speak to their children in the South African context. This study aims at filling this gap. The study adopted a mixed method research design. In-depth interviews and questionnaires were used to generate data. This study was conducted on 10 South African parents who were based in the Gauteng Province. In order to analyse the data, patterns were drawn from the concepts and insights that the participants shared and a research report was written. The findings revealed that these parents and their children strongly identified with English. Furthermore, the parents did not have a positive attitude towards their mother tongues, as these are not global languages. Even though they identified with these languages, they did not see the instrumental value in imparting them to their children because their mother tongues are not really used in official domains. The study gives some recommendations that may aid in improving and solving the language attitudes and ideologies South African parents have about their mother tongue and English.
A Research Report Submitted in Partial Fulfilment of the Requirements for the Award of the Degree of Master of Arts in Applied Linguistics (LING7012A) in the Department of Linguistics, School of Language Literature and Media, University of the Witwatersrand, 2019
Keywords: Linguistics--South Africa; African languages--South Africa